Exsudatos de sementes de soja (Glycine max) como controle potencial de Haemonchus contortus - RIBEIRO, Helen Silva (2018)
Gastrointestinal nematodes of small ruminants cause losses in herd productivity, being a challenge in livestock. Plant compounds have been an alternative to use of commercial anthelmintics, responsible for the selection of resistant parasites. Amoung the compounds presents in different plant parts, the seeds display a broad therapeutic potential. In this context, the Glycine max soybean seeds stand out, given their high production and protein content in the grains. The objective of this study was to evaluate the anthelmintic activity of G.max seed exudates and their fractions enriched with protease inhibitors on Haemonchus contortus. Total exudate (T.SEX) was obtained after immersion of the seeds in 100 mM sodium acetate buffer, pH 5.0, at 5° C for 24 hours. After exhaustive dialysis (cut-off 12 kDa), we obtained the Dialysed Exudate (D.SEX). Finally, after heat treatment of D.SEX, at 100 °C for 10 min, the heated exudate (H.SEX) was obtained. The protein content, the protease inhibitory activity of the exudates, and their action on inhibition of hatchability H. contortus eggs were evaluated. In addition, the inhibitory activity of the exudates on the proteases isolated from the eggs of H. contortus was evaluated. Inhibition of egg hatching was also evaluated using different classes of commercial protease inhibitors [E-64 (10 μM), EDTA (1 mM), Pepstatin A (10 mM) and TPCK (10 mM)]. It was obtained 243.63, 226.88 and 121.67 milligrams of protein per kilogram of seed (mg P/seed Kg) for T.SEX, D.SEX and H.SEX, respectively. The inhibition of the proteases of H. contortus eggs was 31.1, 42.9 and 63.8% for T.SEX, D.SEX and H.SEX, respectively. The protease inhibitor activity of the exudates, using papain as commercial protease, was 41.6, 62.4 and 77.2% for T.SEX, D.SEX and H.SEX, respectively, with EC50 of 0.175, 0.175 and 0.241 mg / mL for T.SEX, D.SEX and H.SEX, respectively. Among commercial protease inhibitors tested, only EDTA and E-64 inhibited hatching of H. contortus eggs (78.98 and 28.86%, respectively). It is concluded that the exudates of G. max seeds have an anthelmintic action and that this action is related to the inhibition of metalloproteases and cysteine proteases of H. contortus eggs.